Insights Into Child Abuse and Neglect in the Washington DC, Maryland, and Virginia (DMV) Area: Evidence and Opportunities - Intima Alrimawi PhD, RN; Elizabeth Bettini PhD, APRN, PCNS-BC; Clishia Taylor DMIN, MBA, RN, CDI, ICTTP; Ahmad Rajeh Saifan PhD, RN; Nabeel Al-Yateem PhD, RN (SAGE Publishing, 2024)
Child abuse and neglect (CAN) significantly impact health, the economy, and society. This narrative review examines CAN in the Washington DC, Maryland, and Virginia (DMV) region, comparing it with national and international levels. The review highlights high CAN rates in the DMV, driven by factors such as socioeconomic status, parental substance abuse, and child vulnerabilities. Screening and reporting challenges, exacerbated by the COVID-19 pandemic, impede accurate data collection. This review emphasizes the need for standardized reporting mechanisms, economic investment in public health, and intersectoral collaboration. It recommends targeted support for at-risk families, specialized care for vulnerable children, and the development of predictive screening tools. Continuous research on regional and cultural factors and the pandemic's impact is crucial for future resilience. Addressing CAN requires a comprehensive approach involving prevention, early detection, intervention, and policy reform to safeguard the well-being of children.